Ionic elastomer based on carboxylated nitrile rubber: infrared spectral analysis - Mandal, U K (Polymer international, 2000)
Carboxylated nitrile rubber (XNBR) neutralized by metal oxide forms an ionic elastomer (ionomer) due to formation of ionic clusters by the metal carboxylated salt. Cluster formation in carboxylated nitrile rubber by metal oxide, mainly zinc oxide (ZnO), has been studied by infrared analyses. Two modes of plasticization, ie plasticization of the hydrocarbon‐rich phase and plasicization of the ionic domains (hard phase), have also been analysed by infrared studies. Results reveal that the cluster formation is stabilized at higher loading of metal oxide with hexacoordinate salt formation and depends on the type of metal oxide. Spectral studies also reveal that a non‐polar plasticizer such as dioctyl phthalate does not affect the characteristic bands of ionic cluster, but polar plasticizers such as dimethylsulfoxide and ammonia solvate the ionic cluster, causing the disappearance of the band corresponding to the hexacoordinated carboxylate salt. Infrared spectral analysis of the ionomer based on carboxylated nitrile rubber (XNBR) further confirms the earlier claims that the profound change in physical properties of the polymer is due to the presence of physical crosslinks generated by ionic clusters. © 2000 Society of Chemical Industry